Calibration of the MOBIL lane changing model with the Krauss car following model using trajectory data - Carigma, Anjilo M.
Simulati ns have been important in predicting the flow of traffic for preparation and modification of current traffic situations. This research makes use of a mathematical model for micro-traffic simulators on the basis of the car following and lane changing concepts, and calibrating such models to fit Filipino traffic. A combination of the stimulus response and safety gap model. Krauss Model was used to predict car following scenario. An acceleration dependent model called the MOBIL was proposed for the lane-changing simulations. The model's ability to simulate realistic traffic flow was confirmed by using flow-density-velocity relationships from the basic transportation theories. Data are to be collected by the fragmentation of video footages of selected traffic phenomena to determine necessary traffic flow characteristics, followed by the execution of genetic algorithm under a chosen objective function to determine the parameters of the two models mentioned. The precision of the determined parameters was checked using simple standard deviation, and the accuracy of tile mode l using the obtained parameters were measured by comparing simulated trajectory from the initial values of pre-obtained empirical data to the actual data.